2004
DOI: 10.1103/physrevlett.93.256602
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transverse Spin Currents in Noncollinear Magnetic Structures

Abstract: We show that the transverse components of spin current in a ferromagnet is linked to an off diagonal spin component of the transmission matrix at interfaces;it has little to do with the mismatch of band structures between dissimilar metals. When we take account of this component,not considered in prior analyses, we find spin torque comes from a region of at lease 3 nm around an interface. It occurs when one drives an electric current across a multilayered structure in which the magnetic layers are noncollinear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 19 publications
(37 reference statements)
4
106
0
Order By: Relevance
“…In the context of the spin Hall effect, the sharp increase in the SOF for very thin FMs may be understood by the finite spindephasing length of the FM. In other words, this result is in accordance with the spin-dephasing effect in the spin torque transfer process 22,23 , where the spin Hall-induced spin current undergoes a Larmor precession because of the exchange interaction with the local magnetization. When the CoFeB is thinner than a characteristic spin-dephasing length, an effective magnetic field can be generated on the magnetization from the spin torque transfer process.…”
Section: Current-induced Magnetization Reorientationsupporting
confidence: 69%
“…In the context of the spin Hall effect, the sharp increase in the SOF for very thin FMs may be understood by the finite spindephasing length of the FM. In other words, this result is in accordance with the spin-dephasing effect in the spin torque transfer process 22,23 , where the spin Hall-induced spin current undergoes a Larmor precession because of the exchange interaction with the local magnetization. When the CoFeB is thinner than a characteristic spin-dephasing length, an effective magnetic field can be generated on the magnetization from the spin torque transfer process.…”
Section: Current-induced Magnetization Reorientationsupporting
confidence: 69%
“…The spin transfer phenomenon, predicted by J. Slonczewski [1] in 1996, is now the subject of extensive experimental [2,3,4,5,6,7,8,9] and theoretical studies [10,11,12,13,14,15]. It has first been shown that a spin polarized current injected into a thin ferromagnetic layer can switch its magnetization.…”
mentioning
confidence: 99%
“…Contrary to this, the free layer could be toggled by passing current or by applying magnetic field. The magnetization dynamics of the MTJ free layer is governed by LLG equation [25] …”
Section: Threat Model (Magnetic Attack)mentioning
confidence: 99%